Tafsir Ayat-Ayat Neurosains Pendidikan Islam: Telaah Tafsir Salman atas Konsep Nashiyah dalam Surat Al-Alaq - Vivi Indri Asrini; Suyadi Suyadi (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
The development of interpretation from time to time has developed, because the mufasir always have views on the interpretation of the Qur'an, one of which is in Al-Alaq's letter about Nasiyah which discusses the brain, therefore this article aims to analyze the concept of Nasiya in Salman's Tafsir which contained in the QS. Al-Alaq verse [96]: 15-16. This research was conducted using qualitative methods and using a library research approach. Data collection techniques through documentation and data collection related to the research conducted, while data analysis techniques are carried out in a hermeneutic manner. The results of this research are arguing that the term of the word Nasiya has appeared long before the Al-Qur'an was revealed, while the term brain only appeared in the 19th century. Therefore, it is not surprising that classical interpretation has not used a neuroscientific approach to understand Nasiya and neuroscience has such a long scientific history, especially in the tradition of Islamic thought both classically and in modern Islamic thought. Given the concepts of Islamic education that need to get special attention which is normative in the area of metaphysics of divinity, which are not yet grounded in the scientific field, so it is still difficult to implement in the pragmatic realm of amalyyah.